Role of Mig-6 in adipose tissue: Implications for glucose metabolism and insulin resistance - Ji Min Kim; Joung Youl Lim; Sorim Choung; Ok Soon Kim; Kyoung Hye Joung; Ju Hee Lee; Hyun Jin Kim; Bon Jeong Ku (PLoS ONE, 2025)
Background Insulin resistance is a hallmark of type 2 diabetes mellitus (T2DM) and is associated with metabolic disorders. Adipose tissue plays a crucial role in regulating whole-body energy balance and glucose homeostasis. Mitogen-inducible gene 6 (Mig-6) is a negative feedback regulator of receptor tyrosine kinases, including epidermal growth factor receptor (EGFR). This study aims to evaluate the role of Mig-6 in white adipose tissue (WAT) and its impact on systemic glucose homeostasis using Mig-6 transgenic mice. Methods Human visceral fat samples were obtained from four obese and three lean women undergoing hysterectomy. Adipocyte-specific Mig-6 knock-in (Mig-6AdKI) mice were generated and maintained on either a high-fat diet (HFD) or normal chow diet (NCD). Glucose tolerance tests (GTT) and insulin tolerance tests (ITT) were performed. We conducted histological examinations to observe tissue morphology and used quantitative PCR to assess adipokine mRNA expression. Results Mig-6 expression was significantly reduced in the adipose tissue of obese mice and humans. Mig-6AdKI mice exhibited improved glucose tolerance and insulin sensitivity under both NCD and HFD conditions, without changes in body weight or fat mass. The improvement in glucose homeostasis under NCD conditions was particularly noteworthy. Increased adiponectin mRNA levels were observed in the WAT of Mig-6AdKI mice. Meanwhile, histological analysis did not observe any changes in adipose tissue morphology that could explain the improvement in systemic glucose homeostasis, although there were tendencies towards increased adipocyte size and inflammation in HFD-fed Mig-6AdKI mice. Conclusion Adipose-specific overexpression of Mig-6 improves systemic glucose tolerance and insulin sensitivity, suggesting its potential as a target for both the treatment and prevention of diabetes. These findings provide a reference for further research targeting EGFR or Mig-6 in adipose tissue, highlighting the metabolic role of Mig-6 in glucose homeostasis.